2013
DOI: 10.1002/aic.14169
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced microbial oil production by activated sludge microorganisms via co‐fermentation of glucose and xylose

Abstract: The co-fermentation of glucose and xylose by activated sludge microorganisms for the production of microbial oils for use as biodiesel feedstock was investigated. Various carbon sources at initial concentration of 60 g/L and C:N ratio 70:1 were investigated: xylose, glucose, and 2:1 and 1:2 (by mass) glucose/xylose mixtures. Oil accumulation ranged between 12 to 22% CDW, the highest of which was obtained when xylose was the sole substrate used. Kinetic modeling of the fermentation data showed that specific gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 33 publications
(38 reference statements)
1
22
1
Order By: Relevance
“…It is necessary to increase the lipid content and biodiesel yield to make it more competitive. A number of factors, such as the type of organic substrate, the organic loading rate, and the ratio of carbon to nitrogen (C:N), influenced the biodiesel production of activated sludge (Mondala et al, 2012(Mondala et al, , 2013. Operational adjustments can be made to create a more favorable environment for accumulation of lipid and production of biodiesel from activated sludge.…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to increase the lipid content and biodiesel yield to make it more competitive. A number of factors, such as the type of organic substrate, the organic loading rate, and the ratio of carbon to nitrogen (C:N), influenced the biodiesel production of activated sludge (Mondala et al, 2012(Mondala et al, , 2013. Operational adjustments can be made to create a more favorable environment for accumulation of lipid and production of biodiesel from activated sludge.…”
Section: Introductionmentioning
confidence: 99%
“…Lipids from the microbial consortia of activated sludge (AS) generated by wastewater treatment plants (WWTP) have been successfully enhanced by aerobic cultivation on a high molar carbon to nitrogen ratio (C/N) using various carbon sources (Fortela et al, ,b; Mondala et al, ; Revellame et al, ; Yook et al, ). Initial studies used sugars as model carbon sources (Mondala et al, ) while recent studies showed that acetic acid can also be a suitable carbon source via fed‐batch cultivation, achieving up to 20% (w/w dry biomass) lipid content (Fortela et al, ). Acetic acid was proposed as an economical carbon source as it is a typical intermediate or by‐product of the anaerobic digestion of organic wastes (Yook et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…5 Apart from the direct water splitting via the semi-conductive photocatalyst that has attracted many interests in the past, 6 the bio-hydrogen process still remains competitive because of its many appealing advantages, ie, cost-effectiveness, simplicity in operations, independence of solar radiation, and highly efficient utilization of renewable lignocellulose. [7][8][9][10] Although efforts of investigating dark hydrogen fermentation have been made for a few decades, there are still quite many spaces left for the optimization of the entire process in the aspect of maximizing the hydrogen yield, minimizing the secondary metabolites inhabitations, and maintaining the stability of the microbes during fermentation. 11,12 In order to enhance the hydrogen yield, different efforts have been trialed by many scholars.…”
Section: Introductionmentioning
confidence: 99%